Handep Hapakat and the Future of Fair Labor Dispute Resolution - Fransisco Fransisco; Hermon Hermon; Eny Susilowati (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study aims to examine the feasibility and normative design of integrating the Dayak philosophy of Handep Hapakat—solidarity, deliberative consensus, and social harmony—into industrial relations dispute resolution, especially at the pre-litigation stage. The research method used is normative legal research employing statutory (legislative), conceptual, and historical approaches. Primary legal materials consist of labor and industrial relations dispute settlement regulations, while secondary materials include scholarly works on Dayak customary law, local wisdom, restorative justice, and legal pluralism. The analysis is descriptive-analytical to construct an integration framework compatible with positive law. The novelty in this research is the formulation of a conceptual integration model that translates Handep Hapakat values into three operational pathways within the existing PPHI structure: (i) customary deliberation-based bipartite settlement (“bipartite plus”), (ii) culturally informed mediation, and (iii) customary arbitration oriented toward restorative outcomes while maintaining legal safeguards. Based on the research, it is concluded that embedding Handep Hapakat can strengthen pre-litigation dispute settlement by promoting faster, lower-cost, participatory resolutions that prioritize relationship repair and reinforce Indonesia’s legal pluralism. Implementation nonetheless requires local regulatory support, systematic stakeholder socialization, and capacity-building for customary leaders to ensure alignment with labor-law standards and rights protection.